MACHIAVELLIANISM AND PERSONAL TRAITS IN YOUNG AGE - Kurapova, Irina; Lezhnina, Larisa (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The article is devoted to one of the vital problems of modern society, the problem of Machiavellianism.  It is noted that manipulative forms of interaction between people become common, and it can lead to a tendency to use the manipulation by an increasing number of people and, in its turn, to the loss of openness, sincerity, and congruence of communication.The results of an empirical study of Machiavellianism and its interrelationship with personality traits in young age are discussed. The study is based on a dispositional approach to the person, suggesting that it consists of reliable, stable, interrelated elements (properties, traits) that determine its internal essence and behavior. Differences in the behavior of people are explained by the differences in the intensity of personality traits. The article shows that adolescence is one of the most sensitive ways to consolidate manipulative strategies in the behavior of a person. The obtained results prove the existence of a interrelationship between Machiavellianism and a number of personality traits, according to the theory of R.B. Cattell. Among such personality traits are communicative (closed), regulative (low normative, low self-control behavior), emotional (rigidity) and intellectual (radicalism). Knowledge of the personal profile of a personality prone to Machiavellianism in adolescence will allow continuing the study within the framework of studying ways of preventing extreme manifestations of manipulative behavior and widening the range of constructive patterns of youth behavior.